The Penguin dictionary of biology - Abercrombie, M. (Penguin, 1980)
A Dictionary of Biology is an up-to-date reference work explains several thousand specialied words that allow for empirical approaches to the biological sciences. It includes more than bare definitions, including information about most of the things named so as to convey their significance in biological discussion. M. Abercrombie, C. J. Hickman, and M. L. Johnson in effect interpret this language as it is actually used, emphasiing customary usage rather than etymology. This comprehensive lexicon includes two thousand entries. Many unfamiliar terms, especially the rarer ones, are defined with the help of other technical terms, perhaps equally unfamiliar. This trick of dictionary-makers could only be avoided by giving a complete account of a large part of biology under each heading. Every biological technical term used in a definition is itself defined elsewhere in the dictionary; though some semi-technical terms, words that can be found in any English dictionary are omitted. The authors use codes throughout the dictionary to help the reader to interpret the use of a word such as whether it is used in relation to plants and animals only, whether the word is an adjective, and when a term is defined elsewhere and adds information to the current definition. The result is an invaluable guide for the layman, the student, and the scholar alike. It presents clear and authoritative explanations of the terms and will remain useful as a quick and concise source of reference.